2009
DOI: 10.1007/s00044-009-9268-7
|View full text |Cite
|
Sign up to set email alerts
|

Facile and manifest spectrophotometric methods for the determination of six quinolone antibiotics in pharmaceutical formulations using iron salts

Abstract: Simple spectrophotometric methods have been developed for the determination of six quinolone antibiotics, namely, ciprofloxacin, gatifloxacin, norfloxacin, levofloxacin, ofloxacin, and pefloxacin, in pharmaceutical formulations using three different salts of iron. These methods are based on the formation of complexes with ferric nitrate, ferric chloride, or iron ammonium citrate in which the carboxylic group of quinolones undergoes complexation with iron. The complexes formed in these reactions, having a brown… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 22 publications
0
13
0
Order By: Relevance
“…These all were quite exclusive methods because of their extended and monotonous pretreatment of the samples, extraction with solvent and derivatization for the analysis of pregabalin. Our research group has reported a number of LC methods for the determination of various drugs as quinolones [13][14][15], cephalosporines [16], Ca channel blockers [17], ACE inhibitors [18][19][20][21] and antidiabetic drugs [22][23][24][25][26][27]. In continuation with this work we report are rapid, sensitive, selective, precise, short time analysis and cost effective RP-HPLC method for the quantitation of pragabalin in API, dosage formulations and human serum, the method is being validated according to ICH guidelines [28,29].…”
Section: Introductionmentioning
confidence: 99%
“…These all were quite exclusive methods because of their extended and monotonous pretreatment of the samples, extraction with solvent and derivatization for the analysis of pregabalin. Our research group has reported a number of LC methods for the determination of various drugs as quinolones [13][14][15], cephalosporines [16], Ca channel blockers [17], ACE inhibitors [18][19][20][21] and antidiabetic drugs [22][23][24][25][26][27]. In continuation with this work we report are rapid, sensitive, selective, precise, short time analysis and cost effective RP-HPLC method for the quantitation of pragabalin in API, dosage formulations and human serum, the method is being validated according to ICH guidelines [28,29].…”
Section: Introductionmentioning
confidence: 99%
“…Generally, UV-vis spectrophotometric determination is the most widely used method for drugs determination in their dosage forms due to its simplicity, low cost and wide availability in laboratories [ 11 ]. Based on the literature review, various methods have been reported for HGAT determination using UV-vis spectrophotometry [ 12 , 13 , 14 , 15 ] but there is few reports describe HGAT determination via its interaction with the metal ions in solution [ 16 ].
Figure 1 The skeleton structure of gatifloxacin, HGAT.
…”
Section: Introductionmentioning
confidence: 99%
“…In the last decade, a number of spectrophotometric methods for the determination of verapamil [17], gabapentin [18], quinolone antibiotics [19], metformin [20], ascorbic acid [21] and montelukast [22] have been developed by our research fellows. In the present study we aimed to describe the rapid and accurate spectrophotometric methods for the determination of three macrolides; ERY, roxithromycin (ROX) and CLR.…”
Section: Introductionmentioning
confidence: 99%